Bridging evidence gaps in attributing loss and damage, and measures to minimize impacts - Engdaw, Mastawesha Misganaw; Mayanja, Brian; Rose, Sabrina; Loboguerrero, Ana Maria; Ghosh, Aniruddha (2024)
Losses and damages from climate change have been increasing as global temperatures continue to rise above pre-industrial levels. Low-income, climate vulnerable countries bear a disproportionate share of these losses and damages. After decades of international negotiations, the Loss and Damage Fund was established in late 2022, aiming at addressing both economic and non-economic losses arising from slow- and sudden-onset climate change events. Recognizing the complex nature of climate-related events, the establishment of the Loss and Damage Fund underscores an urgent need for precise attribution of these events to climate change, highlighting the fund’s reliance on scientific evidence to guide its efforts. Attribution science, which decouples specific causes of changes in climate hazards and impacts, can support loss and damage negotiations. Low-income countries, which have contributed the least to climate change, are experiencing more severe impacts. However, data quality and coverage required for scientific studies to attribute loss and damage to climate change remain limited in these developing countries. In this paper, we highlight the challenges to attribute losses and damages to climate change in developing countries and underscore strategies to overcome those challenges using examples from the agrifood sector. These strategies have implications for the operationalizing of the Loss and Damage Fund. We emphasize how improving data availability and quality can lead to rigorous scientific conclusions, supporting evidence-based, inclusive, and effective interventions. We also indicated measures that enable strengthening climate resilience to avoid and minimize losses and damages.